Voluntary Medical Male Circumcision: An HIV Prevention Priority for PEPFAR - Reed, Jason Bailey (2012)
As the science demonstrating strong evidence for voluntary medical male circumcision (VMMC) for HIV prevention has evolved, the President’s Emergency Plan for AIDS Relief (PEPFAR) has collaborated with international agencies, donors, and partner country governments supporting VMMC programming. Mathematical models forecast that quickly reaching a large number of uncircumcised men with VMMC in strategically chosen populations may dramatically reduce community-level HIV incidence and save billions of dollars in HIV care and treatment costs. Because VMMC is a 1-time procedure that confers life-long partial protection against HIV, programs for adult men are vital short-term investments with long-term benefits. VMMC also provides a unique opportunity to reach boys and men with HIV testing and counseling services and referrals for other HIV services, including treatment. After formal recommendations by WHO in 2007, priority countries have pursued expansion of VMMC. More than 1 million males have received VMMC thus far, with the most notable successes coming from Kenya’s Nyanza Province. However, a myriad of necessary cultural, political, and ethical considerations have moderated the pace of overall success. Because many millions more uncircumcised men would benefit from VMMC services now, US President Barack Obama committed PEPFAR to provide 4.7 million males with VMMC by 2014. Innovative circumcision methods—such as medical devices that remove the foreskin without injected anesthesia and/or sutures—are being rigorously evaluated. Incorporation of safe innovations into surgical VMMC programs may provide the opportunity to reach more men more quickly with services and dramatically reduce HIV incidence for all.